2021
DOI: 10.1097/olq.0000000000001509
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical, Gram Stain, and Microbiological Cure Outcomes in Men Receiving Azithromycin for Acute Nongonococcal Urethritis: Discordant Cures Are Associated With Mycoplasma genitalium Infection

Abstract: Resolution of nongonococcal urethritis signs and symptoms does not always correlate with microbiological cure; discordant cures occur in one third of men. Clinical cure accurately correlates with Gram stain and microbiological cure for NGU bacterial pathogens, except Mycoplasma genitalium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…They observed that clinical cure (loss of symptoms) predicted microbiological cure (Test of cure via NAATs) for those infected with CT, UU, and TV. However, that was not the case for MG, as microbiological failure has been observed in men who experienced clinical cures (21). Macrolide-resistant MG infections were highly linked to microbiological failure (21).…”
Section: Non-gonococcal Urethritismentioning
confidence: 99%
See 4 more Smart Citations
“…They observed that clinical cure (loss of symptoms) predicted microbiological cure (Test of cure via NAATs) for those infected with CT, UU, and TV. However, that was not the case for MG, as microbiological failure has been observed in men who experienced clinical cures (21). Macrolide-resistant MG infections were highly linked to microbiological failure (21).…”
Section: Non-gonococcal Urethritismentioning
confidence: 99%
“…However, that was not the case for MG, as microbiological failure has been observed in men who experienced clinical cures (21). Macrolide-resistant MG infections were highly linked to microbiological failure (21). The authors, therefore, concluded that in azithromycin-treated MG-NGU infected men, the microbiological cure must be gained, at least in those settings where macrolide resistance cannot be tested (21).…”
Section: Non-gonococcal Urethritismentioning
confidence: 99%
See 3 more Smart Citations